Sharia Banking and Sustainable Development Goals: An Empirical Analysis of Socio-Economic Indicators and Inclusive Growth in Aceh Province - Arifa Pratami; Purwanto (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2026)
This study examines whether Aceh’s mandatory Sharia financial system contributes to SDG-related socio-economic outcomes and inclusive growth during the 2020–2024 period. Although Aceh represents a distinctive jurisdiction-level case of Sharia finance, limited empirical evidence explains how Sharia banking intermediation and regional fiscal policy jointly shape welfare outcomes. This study analyzes balanced panel data from 21 districts/cities in Aceh, comprising 105 district-year observations, using fixed-effects models with robust standard errors applied where heteroskedasticity is detected. The results show that Sharia financing is significantly associated with lower unemployment, indicating its role in strengthening labor absorption through productive financial intermediation. The Financing-to-Deposit Ratio (FDR) is positively associated with the Human Development Index (HDI), suggesting that more active Sharia banking intermediation supports human development. However, regional government expenditure is positively associated with the Gini Ratio, revealing a fiscal paradox in which public spending appears insufficiently redistributive. The study concludes that Aceh’s Sharia financial transformation cannot rely solely on banking intermediation; it requires stronger alignment with inclusive fiscal governance. This research contributes to Islamic economics by showing that ethical financial transformation produces broader welfare effects only when supported by redistributive public policy.